Experience with Management of Radial Polydactyly: The Multicenter Analysis of 28 Surgical Procedures with Follow-Up - Breidung, David; Megas, Ioannis Fivos; Dittrich, Yvonne; Reichert, Bert; Nöth, Ulrich; Habild, Götz (Healthcare, 2023)
Radial polydactyly or thumb duplication is a relatively common congenital malformation of the hand, whereby the surgical techniques can be broadly divided into simple excisions, reconstructions and a Bilhaut-Cloquet procedure. The aim of this study was to identify the appropriate surgical procedures and to present the clinical outcomes that can be achieved. We performed a multicenter analysis of cases of radial polydactyly surgically treated with reconstruction or a Bilhaut-Cloquet procedure between 2015 and 2022. The clinical outcome was assessed using a modification of the Tada score. A total of 28 cases of 27 patients with radial polydactyly were included in the study. The most common Wassel type was type IV (13 cases), and the most common surgical procedure was reconstruction (24 cases). Our study validates an algorithm from the literature as a helpful tool for decision making in selecting a surgical technique for radial polydactyly, although individual surgical experience should also be considered.
CRIS-Team Scopus Importer:2023-12-15
Keywords: congenital abnormalities; radial polydactyly; reconstructive surgical procedures; thumb duplication